Metabolomic and lipidomic studies on the intervention of taurochenodeoxycholic acid in mice with hyperlipidemia - Cui, Na; Zhang, Wensen; Su, Fazhi; Zhang, Zhihong; Li, Biao; Peng, Donghui; Sun, Yanping; Zeng, Yuanning; Yang, Bingyou; Kuang, Haixue; Wang, Qiuhong (Frontiers in Pharmacology, 2023)
Bile acids are the main component of animal bile and are directly involved in the metabolic process of lipids in vivo. Taurochenodeoxycholic acid (TCDCA) is the primary biologically active substance in bile acids and has biological functions such as antioxidant, antipyretic, anti-inflammatory, immune, and analgesic. In the present study, we assessed the impact of TCDCA on hyperlipidemia development in murine models. Mice were fed high-fat diet (HFD) to induce hyperlipidemia and orally administered different doses of TCDCA for 30 days. Then, to detect indicators such as triglyceride (TG), total cholesterol (TC), low-density lipoprotein (LDL-C), and high-density lipoprotein (HDL-C) in mice. HE and ORO staining detected the morphology of the mice’s liver tissue. Based on metabolomics and lipidomics, we determined the mechanism of TCDCA in treating hyperlipidemia. The results showed that the TCDCA had a significant ameliorating effect on dietary hyperlipidemia. And it exerted therapeutic effects through glycerophospholipid metabolism.